Pengaruh Kemampuan High Order Thinking Skill Terhadap Hasil Belajar Matematika Siswa Kota Parepare - Wulan Dari (Prodi Pendidikan Matematika Fakultas Keguruan dan Ilmu Pendidikan (FKIP) Universitas Muhammadiyah Parepare, 2023)
This study aims to determine the effect of High Order Thinking Skill on the mathematics learning outcomes of students in class XI UPT SMA Negeri 1 Parepare, while this type of research is quantitative research using the Ex Post Facto approach. The population of this study were all social studies students of class XI UPT SMA Negeri 1 Parepare. The sample in this study amounted to 30 respondents by using a sampling technique is Cluster Random Sampling. The research data was obtained using a research instrument in the form of a description test sheet of 2 numbers to determine the HOTS ability and student learning outcomes. The data collection technique used is a test technique. The data analysis technique used is descriptive statistical analysis and inferential statistical analysis. The results of the descriptive analysis of students of class XI IPS UPT SMA Negeri 1 Parepare were 30 respondents where the students' HOTS ability was in the high category with an average student of 74.83 and a standard deviation of 19.84. The score of students' mathematics learning outcomes is in the medium category with an average student mathematics learning outcome of 76.33 and a standard deviation of 20.08. There is a positive significant effect of HOTS ability on mathematics learning outcomes for students of class XI IPS UPT SMA Negeri 1 Parepare at a significant level = 0.05